Freight forwarding business focused on sea freight export of Kuehne+Nagel Bangladesh Ltd - Talukder, Shahjalal (BRAC University, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.